2016
DOI: 10.1177/1350650116650126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of material heterogeneity on surface fatigue for rough lubricated rolling–sliding contacts

Abstract: In view of increasingly severe operating conditions and the use of composite (strongly) heterogeneous materials, detailed modelling and optimisation methods are needed to predict the effects of subsurface material topology, either by design or resulting from inclusions and material anisotropy, on rolling-sliding contact fatigue life. In this paper, a method is proposed showing that such predictions can at present be obtained for realistic configurations on small-scale computers by integrating efficient numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…The existence of a strong feedback process between the effects of the inclusion and the lubricant's response affecting the von Mises stresses is also highlighted. Furthermore, the numerical results are directly compared with predictions by the semi-analytical model proposed in Morales-Espejel et al., 24 obtaining a reasonable qualitative agreement. However, quantitatively some differences are observed.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The existence of a strong feedback process between the effects of the inclusion and the lubricant's response affecting the von Mises stresses is also highlighted. Furthermore, the numerical results are directly compared with predictions by the semi-analytical model proposed in Morales-Espejel et al., 24 obtaining a reasonable qualitative agreement. However, quantitatively some differences are observed.…”
Section: Discussionmentioning
confidence: 70%
“…First, to investigate by means of full EHL numerical simulations the time-dependent evolution of film thickness and pressure perturbations introduced by moving subsurface inclusions. Second, to verify the rapid, semi-analytical model 24 predictions by direct comparison with full numerical simulations. For the sake of simplicity but without loss of generality, the analysis is limited to a single cylindrical inclusion of varying stiffness in a line contact configuration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of criticality criteria for local material variations/inclusions, and computational diagnostics based on tomographic images. Finally, the developed method can relatively easily be coupled with EHL and study the mutual influence between anisotropic inhomogeneous material and EHL pressure [8,11]…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…They found that the subsurface inclusions changed the EHL pressure and film thickness profiles. Morales-Espejel et al [8] used a rapid micro-EHL methodology combined with a multigrid method for stress calculation and surface deformation [9] to study surface fatigue with heterogeneous material under rough lubricated rolling-sliding contact. The inhomogeneities near contact surface affect pressure and subsurface stress distribution.…”
Section: Introductionmentioning
confidence: 99%